2019
DOI: 10.1038/s41598-019-39246-7
|View full text |Cite
|
Sign up to set email alerts
|

High degree of circular polarization in WS2 spiral nanostructures induced by broken symmetry

Abstract: We present helicity resolved photoluminescence (PL) measurements of WS 2 spiral (SPI) nanostructures. We show that very high degree of circular polarization (DCP) (~94 ± 4%) is obtained from multilayer SPI samples at room temperature upon excitation with a circularly polarized laser at a wavelength near-resonant with the A-exciton (633 nm). TEM analysis showed that these SPI nanostructures have AB stacking in which the inversion symmetry is broken, and hence this leads to very high DCP. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…The maximum DOCP amplitude recorded was 20% and was obtained from the integrated intensities of the 1.94 eV emission component at 4.5 K. By comparison, DOCP amplitudes reported for CdSe/CdS nanocrystals and WS 2 spiral nanostructures were approximately 50% and 96%, respectively. [ 26,27 ] These values suggest the PL was a super‐position of emission components, with one dominant state determining the DOCP. At 1.78 and 1.94 eV, the decrease in DOCP amplitude with increasing temperature was best modelled by a single exponential decay.…”
Section: Resultsmentioning
confidence: 99%
“…The maximum DOCP amplitude recorded was 20% and was obtained from the integrated intensities of the 1.94 eV emission component at 4.5 K. By comparison, DOCP amplitudes reported for CdSe/CdS nanocrystals and WS 2 spiral nanostructures were approximately 50% and 96%, respectively. [ 26,27 ] These values suggest the PL was a super‐position of emission components, with one dominant state determining the DOCP. At 1.78 and 1.94 eV, the decrease in DOCP amplitude with increasing temperature was best modelled by a single exponential decay.…”
Section: Resultsmentioning
confidence: 99%
“…The interband transitions of the K (K ′ ) valley in both upper and lower layers exclusively couple to σ -(σ + ) circularly polarized light. Thus, 3R-stacked TMDCs preserve the same valley-contrasting Berry curvature and physical properties as the case of monolayer, demonstrated recently in 3R MoS 2 [13] and WS 2 spiral nanostructures [27] where the inversion symmetry is broken. Accordingly, 3R-stacked few-layer TMDCs provide an unprecedented candidate for valleytronics and quantum logics [13,[28][29][30].…”
Section: Introductionmentioning
confidence: 57%
“…In contrast to the centrosymmetric AA′ stacking in natural TMDCs crystals, the AB stacking structure possesses broken inversion symmetry, which, as discussed above, is the key factor of a high valley polarization contrast. Barman et al have shown that ≈94 ± 4% of valley polarization contrast can be achieved in WS 2 spiral nanostructure at RT, which is a new record of TMDCs valley polarization contrast observed at RT99 and is much higher than that of bilayer TMDCs (Figure 3d). This discovery widely extends the options of TMDCs nanostructures to be applied in novel valleytronics devices.…”
Section: Valley Excitons and Pseudospins In 2d Tmdcsmentioning
confidence: 78%
“…c) Schematic of AA′ and AB stacking of WS 2 . Reproduced with permission 99. Copyright 2019, Springer Nature.…”
Section: Valley Excitons and Pseudospins In 2d Tmdcsmentioning
confidence: 99%
See 1 more Smart Citation